2009
DOI: 10.1124/jpet.109.162057
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cocaine's Reinforcing and Discriminative Stimulus Effects via Muscarinic M1 Acetylcholine Receptor Stimulation

Abstract: Muscarinic cholinergic receptors modulate dopaminergic function in brain pathways thought to mediate cocaine's abuse-related effects. Here, we sought to confirm and extend in the mouse species findings that nonselective muscarinic receptor antagonists can enhance cocaine's discriminative stimulus. More importantly, we tested the hypothesis that muscarinic receptor agonists with varied receptor subtype selectivity can blunt cocaine's discriminative stimulus and reinforcing effects; we hypothesized a critical ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
74
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(98 citation statements)
references
References 38 publications
21
74
2
1
Order By: Relevance
“…on cue-or methamphetamine-induced reinstatement of responding for methamphetamine, an inhibitory effect that could be counteracted by systemic administration of the nicotinic blocker mecamylamine but not of the muscarinic blocker scopolamine [12]. Finally, the work of Grasing and colleagues is corroborated by Thomsen et al [13] who found that systemic M1-and/or M4-preferring muscarinic agonists flattened the cocaine i.v. FR1 selfadministration curve.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…on cue-or methamphetamine-induced reinstatement of responding for methamphetamine, an inhibitory effect that could be counteracted by systemic administration of the nicotinic blocker mecamylamine but not of the muscarinic blocker scopolamine [12]. Finally, the work of Grasing and colleagues is corroborated by Thomsen et al [13] who found that systemic M1-and/or M4-preferring muscarinic agonists flattened the cocaine i.v. FR1 selfadministration curve.…”
supporting
confidence: 74%
“…Similarly, in the experiments by Crespo et al [23], acquisition of an approach to food was not affected by unilateral intra-accumbens core blockade of nicotinic or muscarinic acetylcholine receptors, whereas an approach to drugs of abuse (cocaine, remifentanil, or morphine) was inhibited by local intra-accumbens muscarinic or nicotinic blockade [22], also arguing against a 'general memory-impairing' effect as the basis for the observed effects on drug reward. Interestingly, Thomsen et al [13] found that the more M1-and/or M4-preferring the antagonist was, the more selective its effect on the expression of responding for cocaine versus food under an FR1 schedule of reinforcement turned out to be.…”
mentioning
confidence: 99%
“…Interestingly, muscarinic agonist-induced reductions in accumbal and striatal DA release are absent in M 4 KO mice, suggesting that M 4 negatively regulates dopaminergic tone in these regions (Threlfell et al, 2010). M 4 KO mice also exhibit deficits in PPI and social interaction and enhanced dopamine D1 receptor-mediated effects on locomotor activity, which are recapitulated in D1-M 4 KO mice (Gomeza et al, 1999;Jeon et al, 2010;Koshimizu et al, 2012;Thomsen et al, 2010). Importantly, the APD-like effects of xanomeline are also abolished in both M 4 KO and D1-M 4 KO mice (Woolley et al, 2009;Dencker et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…Selective stimulation of M 1 or M 4 receptors attenuates cocaine’s discriminative stimulus (S D ) effects and reinforcing effects in rats and mice (Thomsen et al 2010a, 2012, 2014; Dencker et al 2012). Tests using the M 1 /M 4 -preferring agonist xanomeline in knockout mice lacking M 1 receptors (M 1 −/− ), M 4 receptors (M 4 −/− ), or both receptors, indicated that both subtypes are involved in blocking the S D effects of cocaine, while other receptors, likely M 3 , appear to mediate side effects observed with non-selective ligands (Thomsen et al 2010a, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tests using the M 1 /M 4 -preferring agonist xanomeline in knockout mice lacking M 1 receptors (M 1 −/− ), M 4 receptors (M 4 −/− ), or both receptors, indicated that both subtypes are involved in blocking the S D effects of cocaine, while other receptors, likely M 3 , appear to mediate side effects observed with non-selective ligands (Thomsen et al 2010a, 2012). The mechanisms and neural pathways mediating these effects are still poorly understood, but likely involve striatal muscarinic receptors, based on brain region-specific injections using non-selective ligands or cholinergic neuron toxins (Hikida et al 2001; Smith et al 2004; Mark et al 2006).…”
Section: Introductionmentioning
confidence: 99%